2019
DOI: 10.1111/psyg.12464
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of insomnia and its risk factors among older adults in a city in Turkey's Aegean Region

Abstract: Aim: Experienced by many older adults, insomnia is a significant public health problem that requires the attention of health-care professionals and researchers. This study aimed to identify insomnia and its risk factors among community-dwelling older adults. Methods: This cross-sectional study was conducted in Denizli, Turkey. The study sample consisted of 360 elderly individuals aged 60 years and older who were admitted to one of six family health centres for any reason between 29 March 2016 and 17 June 2016.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…In order to reduce its adverse outcomes and allocate appropriate health resources, health professionals and policymakers need to understand the patterns and clinical features of insomnia. Prevalence of insomnia in the general population varies greatly across studies, ranging from 5.8 to 32.8% (18)(19)(20)(21), and is associated with certain demographic factors, such as age, gender, marital status, income, and education level (22).…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce its adverse outcomes and allocate appropriate health resources, health professionals and policymakers need to understand the patterns and clinical features of insomnia. Prevalence of insomnia in the general population varies greatly across studies, ranging from 5.8 to 32.8% (18)(19)(20)(21), and is associated with certain demographic factors, such as age, gender, marital status, income, and education level (22).…”
Section: Introductionmentioning
confidence: 99%
“…Total scores range from 0 to 28, whereby higher scores indicate more severe sleep difficulties. The total score is interpreted as follows: the absence of insomnia (0-7), sub-threshold insomnia (8)(9)(10)(11)(12)(13)(14), moderate insomnia (15)(16)(17)(18)(19)(20)(21), and severe insomnia (22)(23)(24)(25)(26)(27)(28). The ISI has adequate reliability (internal consistency with Cronbach's alpha was 0.79 and testretest reliability for 2 weeks was r = 0.82) and validity in Turkish sample.…”
Section: Beck Depression Inventory (Bdi)mentioning
confidence: 99%
“…Almost half of older adults have been reported to have difficulty initiating or maintaining sleep 11 . The prevalence of insomnia symptoms among older adults is between 23% and 70%, and this rate is higher than the young population 8, 9, 12–14 . Insomnia should be considered as a separate diagnosis when it is not better explained by a psychiatric disorder 15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that it is characterized by di culty in falling asleep, shallow sleep and easy to wake up [4][5][6]. Sleep disorders are extremely common among the elderly, impairing the sleep quality and becoming a public health problem [7,8], seriously affecting the cognitive function of the elderly [9], increasing the risk of falls in the elderly [10]. The demand for sleep has not decrease, it is very common to take sleeping drugs [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%